2016
DOI: 10.1093/aob/mcw046
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput phenotyping (HTP) identifies seedling root traits linked to variation in seed yield and nutrient capture in field-grown oilseed rape (Brassica napusL.)

Abstract: Background and Aims Root traits can be selected for crop improvement. Techniques such as soil excavations can be used to screen root traits in the field, but are limited to genotypes that are well-adapted to field conditions. The aim of this study was to compare a low-cost, high-throughput root phenotyping (HTP) technique in a controlled environment with field performance, using oilseed rape (OSR; Brassica napus) varieties.Methods Primary root length (PRL), lateral root length and lateral root density (LRD) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 75 publications
5
63
0
Order By: Relevance
“…Moreover, attempts should be made to increase the number of experimental repetitions to consolidate the results and their biophysical interpretation (see, e.g., Fig. 5 in Thomas et al 2016). While this has been achieved already for studies involving two-electrode capacitance measurements (e.g., Cseresnyés et al 2016) and four-electrode SIP/EIS measurements (e.g., Postic and Doussan 2016), it is challenging for tomographic, broadband four-electrode impedance measurements given the data acquisition and processing demands.…”
Section: Methodological Considerations For Future Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, attempts should be made to increase the number of experimental repetitions to consolidate the results and their biophysical interpretation (see, e.g., Fig. 5 in Thomas et al 2016). While this has been achieved already for studies involving two-electrode capacitance measurements (e.g., Cseresnyés et al 2016) and four-electrode SIP/EIS measurements (e.g., Postic and Doussan 2016), it is challenging for tomographic, broadband four-electrode impedance measurements given the data acquisition and processing demands.…”
Section: Methodological Considerations For Future Experimental Studiesmentioning
confidence: 99%
“…Neutron radiography has also been successfully used to image live root segments and their surrounding environment (e.g., Moradi et al 2009;Carminati et al 2010). However, these methods are still limited to small sample sizes and laboratory conditions (e.g., Thomas et al 2016), and are subject to high application costs.…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate breeding programs, efficient methods and platforms to screen large breeding populations for meaningful variation at early stages of development would be immensely valuable. Thomas et al (2016) compared a "pouch and wick" high-throughput phenotyping technique to evaluate root traits such as primary root length and lateral root density of 32 elite rapeseed cultivars, along with their root vigor and seed yield, in six field experiments. They concluded that primary root length was the best predictor of early vigor and final seed yield, and that measuring lateral root density could be an additional lever for the improvement of nutrient uptake in rapeseed.…”
Section: Phenotyping For Nitrogen Use Efficiencymentioning
confidence: 99%
“…For instance, young seedling root vigor has been correlated with mature field‐grown root vigor (Wasson et al., ). Seedling root traits have been shown to be linked with mature plant traits such as height and yield in multiple crop species (Bai, Liang, & Hawkesford, ; Thomas et al., ). In this study, we show that two maize cultivars differing in seedling RSA traits exhibited contrasting water‐deficit performance, as evidenced by survival rate, physiological responses, and root system (Figure ; Figure ; Table ).…”
Section: Discussionmentioning
confidence: 99%